Porous phosphomolybdate-based poly(ionic liquid) hybrids with reversible water absorption for enhancement of oxidative desulfurization. (1st February 2023) - Mao, Shao-Xu; Zhou, Qi-Hang; Guo, Hui-Li; Du, Ming; Zhu, Wen-Shuai; Li, Hua-Ming; Pang, Jing-Yu; Dang, Dong-Bin; Bai, Yan
Highlights: Porous phosphomolybdate-based poly(ionic liquid) containing 70% water was firstly synthesized and applied for oxidative desulfurization. Desulfurization efficiency could achieve 100 % at 40 min with lower H2 O2 /S (molar ratio) and catalyst dosage. The effects of water on the microstructure and catalytic activity were systematically investigated, and the water absorption behavior of the catalyst is reversible. Abstract: A novel porous phosphomolybdate-based poly(ionic liquid) catalyst containing 70 % water (PDIM-PMo-W70% ) was assembled with H3 PMo12 O40 (HPMo) and poly-[3-dodecyl-1-vinylimidazolium] bromine (PDIMBr), and characterized by FT-IR, UV–vis, XRD, XPS, Contact angle test, SEM, TEM, TGA, and N2 adsorption–desorption analysis. The turnover frequency (TOF) value of PDIM-PMo-W70% for (dibenzothiophene) DBT removal can reach 41.15 h −1 at 50 °C, which is 35.47 and 9.92 times higher than that of HPMo and PDIM-PMo. The catalyst could be recycled at least five times without a significant change in catalytic activity. The water content of the catalyst, reaction temperature, the molar ratio of H2 O2 /S, catalyst dosage and different sulfur-containing compounds upon oxidative desulfurization (ODS) performance were studied in detail. Most notably, the effects of water on the microstructure and catalytic activity of polyoxometalate-based poly(ionic liquid) were systematically investigated for the first time. As well as the water absorption behavior on the catalyst was reversible, and the dehydrated catalysts after soaking in water could still show excellent catalytic activity. In addition, a reasonable reaction mechanism was proposed with the aid of EPR analysis and radical quenching experiments.